METHODS OF CONDUCTING SCIENTIFIC CREATIVE WORK OF STUDENTS IN THE FIELD OF PHYSICAL CULTURE - Sapayev Ruzmat Radjapovich (Web of Journals Publishing, 2025)
This article is written about the methods of scientific and creative work of physical culture students. In this, the purpose and direct tasks of the scientific-theoretical research occur in a number of individual phenomena, opinions and considerations are given about the laws of the emergence, operation, and development of such phenomena.
Keywords: Method, physical culture, student, science, creativity, research, specialization, personality, education, direction, modernization.